Characterization of the Germplasm Bank for the Spanish Autochthonous Bull Breed “Asturiana de la Montaña” - Carolina Tamargo; Amer Salman; Jose Néstor Caamaño; Felipe Martínez-Pastor; Ángel Fernández; Rodrigo Muiño; María Teresa Carbajo; Carlos Olegario Hidalgo (Animals, 2023)
Semen cryobanks are critical for preserving autochthonous and rare breeds. Since sperm cryopreservation has been optimized for commercial breeds, non-commercial ones (often endangered) must be characterized to ensure the germplasm’s viability. This study reports an investigation of the “Asturiana de la Montaña” breed (AM), a valuable Spanish autochthonous cattle breed adapted to the mountainous Atlantic environment. The survey included cryopreserved semen doses from 40 bulls stored at the Principado de Asturias Germplasm Bank. Data were obtained from the routine fresh semen analysis, CASA (motility), and flow cytometry analyses of fresh and post-thawing semen, and the 56-day non-return-rate (NRR) in heifers and cows (all results as 1st and 3rd quartiles). Fresh samples (artificial vagina) were within the normal range for cattle (4–6 mL, 5–10 × 109/mL; mass motility 5). Post-thawing results showed motility below typical for commercial breeds (total motility 26–43%, progressive 14–28%), with higher values for viability (47–62%). Insemination results showed a good performance for this breed (NRR: 47–56%; higher for heifers). Sperm volume increased with age, with little or no effects on sperm quality. Few associations were found between post-thawing quality or freezability and NRR, LIN being the variable more strongly associated (positively). The AM semen bank shows a good prospect for preserving and disseminating the genetics of this breed. This survey indicates that dedicated research is needed to adapt freezing protocols to this breed, optimizing post-thawing results.